The power of emotional value: Exploring the effects of values on green product consumer choice behavior. (1st May 2017) - Khan, Shamila Nabi; Mohsin, Muhammad
Abstract: Using the theory of consumption values, this research proposes to explore the consumer choice behavior for green products in Pakistan. Functional value (price and quality), social value, conditional value, epistemic value, and emotional value and environmental value were used to study the consumer choice behavior for green products. It also gauges the extent to which emotional value moderates the impact of other consumption values on green product consumer choice behavior. Based on a sample of 260 respondents, the results indicate that functional value (price), social value and environmental value have a positive impact on green product consumer choice behavior, while conditional value and epistemic value have a negative effect. Functional value (quality) and emotional value do not influence green product consumer choice behavior. As a moderator, emotional value has a significant effect on the role of functional value, social value, conditional value, epistemic value and environmental value. This confirms and significantly adds to the literature of green product consumer choice behavior in a developing market. Graphical abstract: Highlights: Functional (price), social and environmental value have a positive effect on green product behavior. Conditional and epistemic value have a negative effect on green product behavior. Functional (quality) and emotional value do not influence choice behavior. Emotional value significantly moderated consumption values and green product consumer choice behavior.